2011
DOI: 10.1017/s0022149x1100054x
|View full text |Cite
|
Sign up to set email alerts
|

The first report on cystic echinococcosis in a cat caused by Echinococcus granulosus sensu stricto (G1)

Abstract: A case of cystic echinococcosis (CE) in a domestic cat is described from Saint Petersburg, Russia. Ultrasonography showed numerous cysts with hyperechoic walls and anechoic contents within the cat's abdominal cavity. Molecular identification based on mitochondrial DNA genes indicated that the causative agent was Echinococcus granulosus sensu stricto (G1 strain). This is the first report of CE in a cat caused by E. granulosus sensu stricto with molecular confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…In Yakutia, G1 has been reported in sheep, and E. intermedius (G6) and E. canadensis (G8, G10) have been found in wild ungulates (including reindeer and elk) and wolves (Konyaev et al, 2013). An unusual case of CE in a domestic cat from St. Petersburg was caused by E. granulosus G1 strain (Konyaev et al, 2012b). E. intermedius (G7) has been reported from Armenia ).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In Yakutia, G1 has been reported in sheep, and E. intermedius (G6) and E. canadensis (G8, G10) have been found in wild ungulates (including reindeer and elk) and wolves (Konyaev et al, 2013). An unusual case of CE in a domestic cat from St. Petersburg was caused by E. granulosus G1 strain (Konyaev et al, 2012b). E. intermedius (G7) has been reported from Armenia ).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…The detailed information (incidence data in each jurisdiction) is listed in (Konyaev et al, 2013); 2 (Sharma et al, 2013); 3 (Konyaev et al, 2012b); 4 (Stefanic et al, 2004); 5 ; 6 (Trachsel et al, 2007); 7 (Ziadinov et al, 2008); 8 Ebi, Gevorgyan H.S., personal communication;…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…However, the genetic diversity of E. granulosus in China has never been characterized based on the complete cytb gene, and only the partial cytb gene have been reported [17,18]. Previous studies demonstrated that both the complete cytb and cox1 sequences showed 1 causative agent of CE in a cat from Russsia, i.e., E. granulosus s.s. (G1) [19]. Therefore, it is feasible that we use the complete cytb gene as a genetic marker to analyse genetic information of E. granulosus .…”
mentioning
confidence: 99%
“…The complete mitochondrial genome of E. granulosus G1 (AF297617), G4 (AF346403), G5 (AB208063), G6 (AB235846) G7 (AB23587), and G8 genotype (AB235848) were served as reference sequences [22,23], and E. multilocularis (AB018440) as the outgroup [24]. Published mtDNA sequences of cytb (AY278067 and AB622276) [17,19] were used for comparison.…”
mentioning
confidence: 99%
“…The infection of intermediate hosts is a result of ingestion of the parasite eggs which shed in the feces of definitive hosts, and the definitive host is infected by ingesting intermediate hosts harboring Echinococcus spp. metacestodes (Konyaev et al, 2012).…”
Section: Introductionmentioning
confidence: 99%